The Role Of Tax Amnesty In Moderating The Effect Of Taxpayer Commitment On Tax Compliance In Individual Taxpayers In Kudus Regency In 2022 - Abdurrosid, Edi Wicaksono; Chandrarin, Grahita; Zuhroh, Diana (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The research objective is to test tax compliance with tax amnesty which moderates the influence of the taxpayer's commitment to tax compliance. The research design uses causality research which serves to represent tax compliance. The research sample used individual taxpayers in Kudus Regency, amounting to 100 respondents. The results of the study explain that the commitment of taxpayers is not able to increase tax compliance. In addition, tax amnesty is capable of moderating which means strengthening the relationship between taxpayer commitments and tax compliance. However, individual taxpayers still perceive that the tax amnesty is not on target, so that in the end the government is advised to issue a tax amnesty policy in the future